The discourse structure and rhetorical strategies used in the construction of an apostate's blog - Azweed Mohamad; Universiti Sultan Zainal Abidin . Faculty of Languages and Communication (2018)
Apostasy is an increasingly alarming issue in Malaysia. The affordance of the internet leads to a new phenomenon whereby apostates use social media to reach the public and other apostates, vent their feeling and frustration, promote their ideologies and beliefs, and question their former religious beliefs. This study aims to provide a thick description of this emerging phenomenon and give insights into how an apostate uses blogs to reach the public, and to examine how readers respond to blog entries. In this qualitative research, an apostate's blog consisting of 21 blog entries, 319 readers' comments, and I 18 responses to the readers' comments were examined using a discourse analysis approach. The analytical lenses employed were digital storytelling, identity construction, and rhetorical strategies. The findings reveal that the blogger is a skillful storyteller who managed to construct engaging entries and responses. The blogger also used the blog as a platform to construct desirable identities in order to reach the public. Ethos (credibility), Pathos (emotion), and Logos (logic) were strategically used to persuade the readers to believe her stories and accept her ideologies. Readers left three types of comment: supportive, 'hate', and advice. 48 per cent of the comments were supportive while only 25 per cent of the comments were negative. The blogger's responses were influenced by the type of comment - positive responses to supportive comments, while ignoring or sarcastically responding to hate comments and unsolicited advice. This study concludes that the apostate's blog postings were more than just the sharing of mundane experiences, rather, the postings were used as a mechanism to obtain support from readers and to construct acceptable identities that could change the public's perception of apostates in general, and herself in particular.
1. Introduction -- 2. Literature review -- 3. Methodology -- 4. Data analysis -- 5. Discussion -- 6. Discussion
Thesis (Degree of Master of English Language Studies) - Universiti Sultan Zainal Abidin, 2018
Includes bibliographical references (p. 129-140)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Languages and Communication -- Dissertations; English language -- Usage; Language and languages -- Usage; Linguistic change; Dissertations, Academic